(3cJGH Gdbdes - (3CHhHcQ eMeO Hf GdSQj Hf Sgd GdeYQha HGHf GdSQGL,J (B316 (3g` s
(3ChdgG (B:s
(3bGd CHh HcQ eMeO Hf GdSQi GdSQGL GdfMhi QMeg Gddg (B: (3EPG CQOJ GdcJGHI aGHJOi HHSe Gddg GdHGA HQCS Gdbde cdg s
(3BNQgG (B:s
(3hcPdc GdaGA hGdhGh hGcJH GdgGA HQCS Gdbde GdCSad Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100 / 2 (3b(B) s
Keywords: (3GdeYGQa GdYGeIs